A Review of Inorganic Hole Transport Materials for Perovskite Solar Cells. Issue 22 (19th October 2018) - Kung, Po‐Kai; Li, Ming‐Hsien; Lin, Pei‐Ying; Chiang, Yu‐Hsien; Chan, Chia‐Ru; Guo, Tzung‐Fang; Chen, Peter
Abstract: This review presents various hole transport layers (HTLs) employed in perovskite solar cells (PSCs) in pursuing high power conversion efficiency (PCE) and functional stability. The PSCs have achieved high PCE (over 23%, certified by NREL) and more efforts have been devoted into research for stability enhancement. Inorganic HTLs become a popular choice as selective contact materials because of their intrinsic chemical stability and low cost. HTLs and electron transport layers (ETLs) are critical components of PSCs due to the requirement to create charge collection selectivity. Herein the authors provide an overview on inorganic HTLs synthesis, properties, and their application in various PSCs for both mesoporous and planar architectures. Inorganic HTLs with appropriate properties, such as proper energy level and high carrier mobility, can not only assist with charge transport, but also improve the stability of PSCs under ambient conditions. The importance of interfacial chemistry and interfacial charge transport is further addressed to understand the underlying mechanism of related degradation and carrier dynamic. It is expected that the success of the inorganic HTL in PSCs can stimulate further research and bring real impact for future photovoltaic technologies. Abstract : The perovskite solar cell (PSC) has boosted its power conversion efficiency along with the application of inorganic hole transport layer (HTL). The presence of inorganic HTL assist the carrier transport and improve the stability. Wide variety of inorganic HTLs are reviewed in this report along with their properties, synthesis technique and interfacial chemistry and carrier dynamic.